Implementasi Teori Sibernetik pada Materi Teks Prosedur di Kelas XI SMAS Karya - Kholis, Muhammad Nur; Jayanti, Rani; Wardani, Dania Kusuma; Khanif, Misbahul; Mayangsari, Salsa Devista (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2023)
This study aims to identify the concrete implementation of cybernetic theory and determine its effectiveness on students' understanding of procedural text learning material in class XI Karya High School. The problem that arises, namely students have difficulty when understanding the ways or stages of making product results presented in the form of writing or text when giving practical assignments on procedure text learning material. This research is a qualitative research with a case study approach. Data collection techniques were in-depth interviews, and direct participant observation. The main source of data came from informants teaching Indonesian language subjects in class XI of SMAS Karya. The research instrument was in the form of questions. The interactive model analysis technique was carried out after collecting research data, namely the researcher reduced the data, presented the data in narrative form, and drew conclusions. After data analysis, data validity was carried out through checking the validity of the data again by ensuring that the data presented was accurate according to the data in the field. The results showed that cybernetic theory was implemented in procedure text material in class XI of Karya Senior High School, namely educators made procedure videos, then showed and presented during learning. Effective understanding has been obtained by students which can be known from the questions raised by educators and observed from the success of making practice videos and presenting product results. Therefore, the learning material of procedure text not only includes how to compile instructions, but also how learners can effectively communicate and collaborate in a digital environment.